From Prototypical Stimuli to Iconographic Stimuli: The Power of Images in the Study of Social Representations - Ida Galli; Roberto Fasanelli (Peoples' Friendship University of Russia (RUDN University), 2021)
When we are interested in the image of a social object, we are interested in what individuals have perceived about that object, the ways in which they have interpreted those perceptions, and what they think about that object. Fully agreeing with the idea that the use of iconographic stimuli can enhance the traditional methods and techniques that are used to study any social representation, in this article, two techniques will be presented. The first, the prototypical stimuli technique, was proposed in the second half of the 1980s by Galli and Nigro. The second technique, iconographic stimuli, creatively integrate images and words in a single tool, was designed more recently to study the social representation of culture by Galli, Fasanelli, and Schember. Researches here reviewed clearly shows that the image has the great power to attract to itself the very objects depicted, a power that the word often does not possess. It is images that make people reflect, help them to think about issues concerning the fundamental aspects of everyday life. The work here presented, carried out in first person by the writer, as well as by all the other authors who are concentrating their efforts in this direction, only represents a starting point of reflection. New and more articulated studies will be able to support with heuristic evidence what so far seems to be configured as a suggestive hypothesis, which in any case will require a wider and shared interdisciplinary effort.